Introducing the Small-Scale Chemistry Approach Through Inquiry-Based Laboratory Activities For Pre-Service Teachers - Fitria Fatichatul Hidayah; Muhamad Imaduddin; Eko Yuliyanto; Gunawan Gunawan; Muhammad Cholid Djunaidi (EduChemia (Jurnal Kimia dan Pendidikan), 2022)
This study introduces a small-scale chemistry (SSC) approach to inquiry-based practicum activities. SSC was introduced to train PCTs' laboratory skills so that they can be creative when teaching in schools in situations where it is not possible to obtain standard lab facilities. The research method is an action research model that includes four stages in the inquiry training process, namely (1) prescription-based practicum learning; (2) small-scale practical demonstrations; (3) small-scale chemistry practicum mentoring; (4) design and implementation of small-scale practicum designs. This research involved 15 Pre-service Chemistry Teachers (PCTs) who were in the Basic Chemistry practicum course. Data collection used documentation techniques for practical activities with an SSC approach, activity response interviews, and open response questionnaires. Instrument validity used face validity, while reliability was obtained by stability of observations. The results of the documentation and interviews were described as narrative, while the responses to the questionnaire were recapitulated and analyzed to obtain a bar chart. Videos were checked using the adequacy rubric which includes performance and procedures. 15 types of chemistry practicums with the SSC approach have been obtained. PCTs have also been able to choose the types of materials that are not only found specifically in the laboratory, but also materials that are easily found in daily lives to be used in school chemistry practical topics. PCTs also reflected that their understanding of the concept is getting better with practicals that are easy to do and their interest in implementing it further.